Development of automated cadastral database selection and visualization system to support the realization of modern cadastrate in malaysia - Omar, Abdullah Hisam; Abdul Mukhshin, Ruzaimi; Abd. Kadir, Abd. Majid; Teng, Chee Boo; Sidek, Rosni Zamuddin Shah; Keling, Noraidah; Saat, Norzalina; Abd. Aziz, Hartini; Yahaya, Noor Anim Zanariah; Muhd. Sahapini, Noor Fadhilah; Buang, Megat Khairun (Faculty of Geoinformation Science And Engineering, 2006)
The process of extracting land records information especially cadastral data for a large number of land title was tedious and time consuming. The development of State Digital Cadastral Database (SDCDB) by Department of Survey and Mapping Malaysia (DSMM) is one of the initiatives to shift to modern cadastral system. Cadastral data need to be adjusted in order to verify the network closure. In order to move to a new adjustment approach, a so-called Least Squares, an Intelligence Based Automated Cadastral Database Conversion System must be developed. The automated functions of the said system are;i) generate of zones and overlapping areas, ii)extracting cadastral information from existing SDCDB,iii) automatically conduct an intelligence cadastral survey concept self- checking procedure, iv) re-compute or rebuild the cadastral records based on mathematical cadastral survey rules, v) automatically prepare corrected data input files ( SDCDB and GPS) for a particular zone and vi) reformatting of data for input into least squares adjustment software. The advantages of automation can be exploited in order to solve or to minimize the needs of manual approach. In order to support the development of survey accurate cadastral system, an automatic programming approach will be adopted. Database selection system will conduct several outliers integrity checking, rebuild cadastral spatial topology (cadastral lot) and make selfcorrection procedures based on cadastral survey concepts and mathematical model respective to the cadastral lots selected. This is to ensure that all cadastral lots are kept in a closed polygon and provide accurate and "clean" cadastral information.. This system was developed in windows environment. Analyses show that the system is functional efficiently. This system is essential and important towards the implementation of computerized Coordinated Cadastral System in Malaysia and it is highly depends on the automated system.. Therefore an Intelligence Based Automated Cadastral Database Selection System is highly potential as a main system application for DSMM or private sector.